Effect of Painful and Non-Painful Sensorimotor Manipulations on Subjective Body Midline - Bouffard, Jason; Gagné, Martin; Mercier, Catherine (Frontiers in Human Neuroscience, 2013)
Patients with chronic pain often show disturbances in their body perception. Understanding the exact role played by pain is however complex, as confounding factors can contribute to the observed deficits in these clinical populations. To address this question, acute experimental pain was used to test the effect of lateralized pain on body perception in healthy subjects. Subjects were asked to indicate the position of their body midline (subjective body midline, SBM) by stopping a moving luminescent dot projected on a screen placed in front of them, in a completely dark environment. The effect of other nonpainful sensorimotor manipulations was also tested to assess the potential unspecific attentional effects of stimulating one side of the body. SBM judgment was made in seventeen volunteers under control and three experimental conditions: 1) painful (heat) stimulation; 2) nonpainful vibrotactile stimulation; and 3) muscle contraction. The effects of the stimulated side and the type of trial (control vs. experimental condition), were tested separately for each condition with a 2 x 2 repeated measures ANOVA. The analyses revealed a significant interaction in both pain (p = 0.05) and vibration conditions (p = 0.04). Post-hoc tests showed opposite effects of pain and vibration. Pain applied on the right arm deviated the SBM toward the right (stimulated) side (p = 0.03) while vibration applied on the left arm deviated the SBM toward the right (not stimulated) side (p = 0.01). These opposite patterns suggest that the shift in SBM is likely to be specifically linked to the stimulation modality. It is concluded that acute experimental pain can induce an SBM shift toward the stimulated side, which might be functionally beneficial to protect the painful area of the body. Interestingly, it appears to be easier to bias SBM toward the right side, regardless of the modality and of the stimulated side.